2006
DOI: 10.1158/1055-9965.epi-05-0864
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Cervical Disease Progression of French Women Infected with the Human Papillomavirus Type 16 E6-350G Variant

Abstract: To test the significance of human papillomavirus (HPV) type 16 and HPV16 E6 variants as risk factors for viral persistence and progression to high-grade lesion, we did a nested case-control study within a cohort study of >15,000 Caucasian French women. Three groups infected with highrisk HPV were compared: (a) women with cleared infection (controls, n = 201), (b) women with persistent infection (cases, n = 87), and (c) women who progressed into highgrade lesion (cases, n = 58 A subgroup of human papillomavirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 33 publications
8
82
1
1
Order By: Relevance
“…In a previous study of 95 HPV16-positive women identified through routine screening in France (23), no statistically significant differences in risk for HPV16 persistence were identified by variant status. However, the definition of HPV16 persistence was less well defined than in the present study (i.e., persistent at 2 years) and 95% confidence intervals remain compatible with the present findings.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a previous study of 95 HPV16-positive women identified through routine screening in France (23), no statistically significant differences in risk for HPV16 persistence were identified by variant status. However, the definition of HPV16 persistence was less well defined than in the present study (i.e., persistent at 2 years) and 95% confidence intervals remain compatible with the present findings.…”
Section: Discussionmentioning
confidence: 76%
“…The most common individual polymorphism in E6 is 350G that leads to a change from leucine to valine at codon 83 (L83V), which defines two distinct sublineages within the EUR lineage (20,21). Some studies have suggested that the EUR-350G and EUR-350T sublineages vary in their distribution between cervical cancers and controls (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…These differences have been elucidated most clearly for HPV16. Multiple studies have shown that HPV16 variants differ in their association with cervical cancer (Tidy et al, 1989;Berumen et al, 2001;Zehbe et al, 1998aZehbe et al, , b, 2001Kammer et al, 2002;Xi et al, 2007), viral persistence (Grodzki et al, 2006;Xi et al, 2006;Lee et al, 2008) and the frequency of recurrence of cervical disease (Xi et al, 2007). Increased risk of anal cancers has also been reported for certain HPV16 variants (Xi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Independent genetic and epidemiological studies have demonstrated the existence of natural variations in the HPV genome. These HPV16 variants seem to be risk factors for viral persistence; this is probably because of modification of the immunogenic properties of the virus (Grodzki et al, 2006). In fact, differential pathogenicity of HPV16 variants with mutations in E6 has been reported for cervical high-grade squamous intraepithelial lesions (HSIL), invasive cervical cancer and anal HSIL (Da Costa et al, 2002;Grodzki et al, 2006;Wu et al, 2006;Zehbe et al, 1998;Zuna et al, 2009 HPV16 induce markedly faster dividing when grown as organotypic raft cultures (Asadurian et al, 2007;Zehbe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%